2018
DOI: 10.1016/j.jcma.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rheumatoid arthritis on the risk of cerebrovascular disease and coronary artery disease in young adults

Abstract: RA is an independent risk factor for CVD/CAD in young adults. The government should develop policies for preventing early onset hypertension to reduce the incidence of CVD/CAD among young patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The association between these conditions is previously described [52]. The association between stroke and RA in example 2 is also previously described [53, 54]. A disease cluster of cardiovascular diseases, metabolic diseases and mental health problems similar to that used in example 3, has previously been pointed out in a Norwegian population-based study on multimorbidity [18].…”
Section: Discussionmentioning
confidence: 90%
“…The association between these conditions is previously described [52]. The association between stroke and RA in example 2 is also previously described [53, 54]. A disease cluster of cardiovascular diseases, metabolic diseases and mental health problems similar to that used in example 3, has previously been pointed out in a Norwegian population-based study on multimorbidity [18].…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, other large studies of cancer overall have also shown no increased (20,43,44) or net decreased risk of cancer (45). Finally, the presence of an association between several comorbidities and RA in this study served as a reassuring positive control given established connections from RA literature including asthma (46), COPD (47), CAD (48), GERD and thyroid disease (20), ILD (49), obesity (18), and neuropathy, including vasculitic neuropathy (50), peripheral neuropathy (51), and carpal tunnel syndrome (52).…”
Section: Discussionmentioning
confidence: 94%
“…RA is an independent risk factor for MI in young adults [21] , [22] . A recent meta-analysis demonstrated that patients with RA had significantly increased risk of CAD (RR = 1.26 [95% CI 1.04–1.52]; p = 0.021) compared to controls [23] .…”
Section: Discussionmentioning
confidence: 97%